Single Earthquake Bond Pricing Framework With Double Trigger Parameters Based On Multi Regional Seismic Information - Wulan Anggraeni; Sudradjat Supian; Sukono; Nurfadhlina Abdul Halim (MDPI, 2024)
Indexed by WOS/ Scopus